Redundancy Prevention and Secure Audit of Encrypted BigData in HDFS Cloud using CloudGaurd+ System - Atul Shevade, Vinit; A. Kulkarni, D (International Journal of Engineering and Technology, 2018)
The recent emerging Cloud Storageand Computing Technology provides a better approach for administrations and service provisioning over the Internet byoffering various computing and storage resources. The key significant and favored cloud service’s is information storage. Therefore, to maintain and conserve the privacy of data owners, data is often encrypted and stored onto the cloud as ciphered data. Nevertheless, a ciphered data introduces some issues for cloud data redundancy, which has been proved to be critical for Bigdata storage and computation in cloudenvironment. Conventional redundancy prevention methods do not work efficiently over ciphered data. Existing systems forciphered data redundancy prevention raises security issues and eventually effects the cloud processing. These existing systems are not capable of efficiently handling data access control and revocations. Therefore aiming to overcome these issues and achieving both redundancy prevention and integrity of cloud data, in this paper we propose a system, namely CloudGaurd+, to prevent redundancy of the stored ciphered data in HDFS Cloud based on authentication provocation and cryptography techniques. CloudGaurd+ incorporates cloud information redundancy prevention with access control. We assess its efficiency and performance based on substantial analysis and computer programming and simulations. The investigation and reenactment comes about demonstrates the unrivaled productivity and adequacy of the CloudGaurd+ system for  prospective deployment practically , particularly for Bigdata redundancy prevention in HDFS distributed cloud storage can be achieved.
Keywords: Redundancy Prevention; Cloud Storage; File Access Control; BigData; Data-Tag.